2023
DOI: 10.4236/pp.2023.142003
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Mycobacterial Activity of Medicinal Plant Extracts Used in the Treatment of Tuberculosis by Traditional Medicine Practitioners in Uganda

Abstract: Tuberculosis (TB) remains a public health challenge and one of the leading causes of death worldwide. TB is preventable and curable. However, treatment of tuberculosis has continued to be difficult as a result of rapid increase of multidrug and extensively drug resistant strains of Mycobacterium tuberculosis. Medicinal plants have for centuries been traditionally used in treatment of tuberculosis and similar ailments. They possess antimicrobial properties which render them a new hope as a source of novel bioac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
(21 reference statements)
1
2
0
Order By: Relevance
“…This nding was consistent with other standard anti-TB drugs studied against MDR strains. This is in tandem with other previous studies that indicated that extracts of Z. leprieurii and R. cordifolia inhibited the growth of the MDR strain of Mycobacterium tuberculosis [4,20,22].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This nding was consistent with other standard anti-TB drugs studied against MDR strains. This is in tandem with other previous studies that indicated that extracts of Z. leprieurii and R. cordifolia inhibited the growth of the MDR strain of Mycobacterium tuberculosis [4,20,22].…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, there is a global imperative to discover and develop new and e cacious antituberculosis agents, which should be an urgent biomedical priority [18,19]. The plants selected in the current study are commonly used in Ugandan traditional medicine to treat tuberculosis and related ailments and have also been studied for their antimycobacterial activity against different strains of Mycobacterium tuberculosis [4,10,20]. However, little is known about the effects of combination of medicinal plants and conventional antituberculosis drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation